Crack tip stress based kinetic fracture model of a PVA dual-crosslink hydrogel. (May 2019) - Liu, Mincong; Guo, Jingyi; Hui, Chung-Yuen; Zehnder, Alan
Abstract: The Mode I fracture of a dual-crosslink hydrogel under creep and constant stretch rate loading is investigated experimentally. The hydrogel network contains both permanent, or chemical, bonds and transient, or physical bonds that are constantly breaking and reforming. The resulting material is highly viscoelastic and capable of deforming to large strains prior to failure. Finite element and asymptotic analyses of the crack tip stress fields are used to calculate a stress intensity factor like crack tip parameter. Using this parameter in a kinetic model of failure in which the rate of bond breaking depends exponentially on the stress level, results from creep fracture tests are used to develop a fracture criterion that is then applied to predict failure under constant stretch rate loading conditions.